The Role of Echocardiography in the Diagnosis of Cardiorheumatological Diseases in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Echocardiography (ECHOCG) is an ultrasound examination of a child's heart. This examination is also called "ultrasound of the heart". It is the main tool of cardiologists for non-invasive assessment of the condition of the heart and the quality of its work